2022
DOI: 10.1038/s41533-022-00306-7
|View full text |Cite
|
Sign up to set email alerts
|

Addressing sex and gender to improve asthma management

Abstract: Sex (whether one is ‘male’ or ‘female’, based on biological characteristics) and gender (defined by socially constructed roles and behaviors) influence asthma diagnosis and management. For example, women generally report more severe asthma symptoms than men; men and women are exposed to different asthma-causing triggers; men tend to be more physically active than women. Furthermore, implicit, often unintended gender bias by healthcare professionals (HCPs) is widespread, and may result in delayed asthma diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Despite this, we did achieve a postrandomization balance in recorded characteristics at baseline, indicating successful randomization. Most of the participants were female, reflecting established differences in sex-specific rates of asthma [ 42 ], health behaviors, and health care use in adults [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, we did achieve a postrandomization balance in recorded characteristics at baseline, indicating successful randomization. Most of the participants were female, reflecting established differences in sex-specific rates of asthma [ 42 ], health behaviors, and health care use in adults [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This sex difference in asthma control has been demonstrated previously in adults 19 and adolescents 20 and is suggested to be caused by sex-specific physiologic differences and sex-specific behavioral differences. 21 Standardized questionnaires such as the ACT are useful tools to assess asthma symptoms. Still, the ACT is insufficient for a complete assessment of asthma control, as exacerbations and pulmonary function are not included.…”
Section: Discussionmentioning
confidence: 99%
“…17 Men are more likely to be exposed to pyrolysis products, plant-based materials, isocyanates, metals, and metalloids. 18 It is thought that the stimuli causing occupational asthma are also different due to the fact that men and women work in different work environments. In this study, unlike the literature, occupational asthma was found to lead to higher mortality and DALYs in men.…”
Section: Discussionmentioning
confidence: 99%